Pengembangan Media Pembelajaran Interaktif Materi Pengenalan Komponen PC pada Siswa Kelas X TKJ SMK Negeri 5 Malang - Suryo Utomo; Hanifah Muslimah Az-Zahra; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
When implementing PPL at State Vocational High School 5 Malang, many students find it difficult to take lessons in the introduction of Personal Computer (PC) components because class X is still unfamiliar with the components of Personal Computer (PC) devices that when they were in middle school they had not learned about any components that are in the Personal Computer because of the limited facilities and infrastructure. So that these deficiencies can be overcome and covered, an Interactive Learning Media (MPI) product is created using the APPED model. This APPED model consists of 5 systematic and logical steps, namely: Initial Analysis and Research, Design, Production, Evaluation, Dissemination. Based on the respondents 'pre tes results, students' completeness is determined by KKM. Completeness of the pre tes scores of two respondents, 70 with the category